The Effect of Soccer Training on the Development of Gross Motor Skills of Senior High School Students - Nur Annisa; Muh. Takbir Adha; Ikra Saputra; Fachrul Rozy; Agus Awal Putra (Journal of Physical Education, Sport, and Human Performance, 2025)
Introduction. Gross motor developments is an important aspect in adolescence because it is related to basic physical abilities that support motor activities such as running, jumping, kicking, and maintaining balance. The low physical activity of students in schools, including at SMAN 4 Takalar, causes gross motor skill to not develop optimally. Soccer training is a from physical activity that involves body coordination, large muscle strength, and agility, thus potentially improving adolescents’ gross motor skills. This study aims to analyze the effect of structured soccer training on the gross motor skills of students at SMAN 4 Takalar. Methods. The study used a quasi-experimental design with a pre-test and post-test approach. The sample consisted of 12 students selected by purposive sampling from 32 extracurricular soccer participants. The program intervention lasted for 30 minutes in one meeting. Gross motor ability data were collected through p hysical tests, including agility and speed. Data analysis used descriptive statistics and a sample t-test with a significance level of  0.05 Results. The results showed a significant increase in students’ agility and speed abilities, with a decrease of 0.45 seconds and 0.64 seconds, respectively (p< 0.05), indicating increased movement efficiency, increased muscle freezing strength, and better body coordination. Conclusion. Structured soccer training has a positive effect on students' gross motor development, especially in the aspects of agility and speed. Therefore, soccer training is recommended as part of the Physical Education program in schools to support physical development and fitness.